(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
Neologisms play a crucial role in linguistic evolution, reflecting social, cultural, and technological changes. This paper explores the various classifications of neologisms based on linguistic theories, particularly focusing on English and Uzbek languages. The study analyzes word formation processes such as affixation, compounding, borrowing, and semantic shifts. The comparative approach highlights similarities and differences in neologism formation between two languages. By employing a qualitative comparative methodology, the paper provides insights into the role of neologisms in linguistic enrichment and their impact on communication.